ANALISIS PERAN DANA DESA DAN ISLAMIC HUMAN DEVELOPMENT INDEX (I-HDI) TERHADAP TINGKAT KEMISKINAN (STUDI KASUS PADA PROVINSI JAWA TIMUR PERIODE 2018 - 2022) - Hayatuzzahrah Taqiyyah; Sri Muljaningsih (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Poverty is still a major problem today in the economy. This problem is increasing with the COVID-19 pandemic. The solution to poverty alleviation is carried out by the government, namely the allocation of village funds. In addition, poverty alleviation can be seen from human resources which is a factor in poverty, namely the Islamic Human Development Index by applying aspects of Maqashid Syariah. The purpose of this study is to see how the influence of village funds and the Islamic Human Development Index on poverty alleviation in East Java Province. This research is quantitative using panel data analysis with variables of village funds, Islamic Human Development Index (X variable) and poverty rate (Y variable). The research was conducted in 29 districts in East Java in the period 2018-2022. The result of this study is the selection of fixed effect model. Furthermore, the village fund variable has a negative and significant influence on the poverty rate in East Java. The Islamic Human Development Index variable has a negative and insignificant effect on the poverty rate. This result is expected to be an effective solution for poverty alleviation through village funds in order to maximize allocation and the Islamic Human Development Index has a further impact on poverty alleviation. Keywords: Village funds; I-HDI; Poverty; Allocation